1991
DOI: 10.1139/z91-009
|View full text |Cite
|
Sign up to set email alerts
|

Modification of stream ecosystem structure and function by beaver (Castor canadensis) in the Adirondack Mountains, New York

Abstract: SMITH, M. E., DRISCOLL, C. T., WYSKOWSKI, B. J., BROOKS, C. M., and COSENTINI, C. C. 1991. Modification of stream ecosystem structure and function by beaver (Castor canadensis) in the Adirondack Mountains, New York. Can. J. Zool. 69: 55-61. Stream ecosystem structure and function were studied in an acidic second-order Adirondack Mountain stream system with current beaver activity. Acid-neutralizing capacity, pH, dissolved organic carbon, ~e~+ , and ~n~+ values were elevated and SO$-, Aln-, and dissolved oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Rural ponds in Michigan, United States increased stream temperatures to a similar degree (-1-5°C), and were associated with changes in invertebrate community composition (Lessard & Hayes 2003). Smith et al (1991) found increased stream temperature and reduced DO and benthic invertebrate species richness 1 m downstream of a beaver pond. Alexander (1998) also found significant increases in stream temperatures and effects on the invertebrate community below two beaver ponds.…”
Section: Discussionmentioning
confidence: 91%
“…Rural ponds in Michigan, United States increased stream temperatures to a similar degree (-1-5°C), and were associated with changes in invertebrate community composition (Lessard & Hayes 2003). Smith et al (1991) found increased stream temperature and reduced DO and benthic invertebrate species richness 1 m downstream of a beaver pond. Alexander (1998) also found significant increases in stream temperatures and effects on the invertebrate community below two beaver ponds.…”
Section: Discussionmentioning
confidence: 91%
“…The macroinvertebrate communities in beaver ponds are reported to be considerably different from those in unimpounded sections [5,6]. Beaver dams affect stream habitats by slowing down the current, increasing depth and width, and creating an environment more similar to lentic systems [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing benthic stream invertebrate assemblages upstream and downstream of beaver ponds (McDowell & Naiman, 1986;Smith et al, 1991;Clifford et al, 1993;Margolis et al, 2001a) often report inconsistent effects. For example, previous studies have reported higher densities of invertebrate suspension feeders downstream of beaver ponds (Clifford et al, 1993;Margolis et al, 2001a), no significant changes in suspension feeder abundance (McDowell & Naiman, 1986), or decreased abundance downstream (Smith et al, 1991). Comparative studies are needed to identify factors potentially explaining the variation among observed effects of beaver ponds on downstream ecosystems.…”
Section: Introductionmentioning
confidence: 99%